2003
DOI: 10.1097/00001756-200303240-00013
|View full text |Cite
|
Sign up to set email alerts
|

Neural prosthetic control signals from plan activity

Abstract: The prospect of assisting disabled patients by translating neural activity from the brain into control signals for prosthetic devices, has flourished in recent years. Current systems rely on neural activity present during natural arm movements. We propose here that neural activity present before or even without natural arm movements can provide an important, and potentially advantageous, source of control signals. To demonstrate how control signals can be derived from such plan activity we performed a computat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
127
1
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(131 citation statements)
references
References 20 publications
0
127
1
3
Order By: Relevance
“…As noted in the subsections above, there are several key differences between our internally-paced system and that in Shenoy et al (2003). These are summarized below.…”
Section: Summary Of Advancesmentioning
confidence: 96%
See 2 more Smart Citations
“…As noted in the subsections above, there are several key differences between our internally-paced system and that in Shenoy et al (2003). These are summarized below.…”
Section: Summary Of Advancesmentioning
confidence: 96%
“…This is because if the predicted appearance time differs from the actual appearance time, then the target estimator will use spike rate data from outside the time range used in building the target prediction model. Note that this differs from the time transition rule in Shenoy et al (2003) since it uses 200 ms of activity instead of 500 ms.…”
Section: The Fixed Window Rulementioning
confidence: 99%
See 1 more Smart Citation
“…Development is rapid, both on the hardware side, where multielectrode recordings from more than 300 electrodes permanently implanted in the brain are currently state-of-the art, and on the software side, with computers learning to interpret the signals and commands (Nicolelis et al 2003;Shenoy et al 2003;Carmena et al 2003). Early experiments on humans have shown that it is possible for profoundly paralyzed patients to control a computer cursor using just a single electrode (Kennedy and Bakay 1998) implanted in the brain, and experiments by Parag Patil and colleagues have demonstrated that the kind of multielectrode recording devices used in monkeys would most likely also function in humans (Peterman et al 2004;Patil et al 2004).…”
Section: Brain-computer Interfacesmentioning
confidence: 99%
“…Research has been made on interfaces that connect to cognitive cortical signals, and on devices that respond to specific plans and intentions of motor tasks, rather than on the neural execution of those tasks (e.g. Hatsopoulos et al 2004;Musallam et al 2004;Shenoy et al 2003). One could presume that devices functioning on the basis of conscious intentions would prove to be very useful indeed, for such intentions could be executed in a variety of ways, and they could thus allow a variety of different concrete implementations; indeed, the fruitfulness of this approach has recently been demonstrated on a human subject (Aflalo et al 2015).…”
Section: A Crash Course In Neuroprostheticsmentioning
confidence: 99%